Strategi Integrasi Hotel Syariah dan Restoran Halal dalam Meningkatkan Kunjungan dan Kepuasan Tamu: (Studi Kasus pada Hotel Mangkuto Syariah Payakumbuh) - Muhammad Hendra; Helmi Ali; Hendra Lukito; Dona Amelia; Gusrizal Gazahar (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The development of halal tourism has encouraged sharia hotels to provide services that are not only comfortable and functional, but also consistent with Islamic values and halal assurance. This study aims to analyze the integration strategy between sharia hotels and halal restaurants in increasing guest visits and satisfaction at Mangkuto Sharia Hotel Payakumbuh. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving hotel management, operational employees, guests, sharia certification experts, and representatives of the local government. The data were analyzed descriptively and strengthened through strategic analysis using the Resource-Based View (RBV), Value Chain, SWOT analysis, IFAS-EFAS matrix, TOWS matrix, and Blue Ocean Strategy. The findings reveal that service integration was implemented through sharia-based operational policies, halal assurance systems in restaurant activities, and cross-departmental coordination between the front office, housekeeping, and food and beverage departments. This integration created added value in the form of physical comfort, emotional trust, and spiritual peace for guests. Internal hotel data also indicated an increase in occupancy rates from 26% in 2020 to 52% in 2024 following the implementation of the sharia concept and halal restaurant integration. Strategic analysis positioned the hotel in Quadrant I (aggressive growth strategy), supported by its halal reputation, Islamic organizational culture, guest trust, and its uniqueness as the first sharia hotel in West Sumatra certified by the National Sharia Council–Indonesian Ulema Council (DSN-MUI). The implication of this study shows that the integration of sharia hospitality can serve as a competitive product strategy rather than merely a compliance instrument, while also supporting the development of regional halal tourism.